Identifying hate speech of Bangla language text using natural language processing - Rahman, Mushfiqur; Jui, Razia Sultana; Sakib, Chowdhury Nazmuz; Ridoy, Fahim Alavi; Ananya, Taskiea Tabassum (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.